2022
DOI: 10.1111/hsc.13712
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional analysis of factors associated with stress, burnout and turnover intention among healthcare workers during the COVID‐19 pandemic in the United States

Abstract: the health, economic and social consequences of the COVID-19 pandemic were ubiquitous across the United States Hospitalisation and infections rates quadrupled between November and December, overwhelming healthcare systems (CDC, 2021).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 74 publications
2
25
1
Order By: Relevance
“…Mirzaei et al [ 51 ] also noted that male nurses experienced turnover intention at a higher rate. While two American studies found that seniority in nurses was associated with greater turnover intention [ 34 , 50 ], this was in contrast to findings in a study from Peru [ 67 ], which reported that younger HCWs were more prone to experiencing turnover intention. Social affiliation was also identified by some studies to impact turnover intention, as nurses with strong ties to friends and family perceived greater social support.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…Mirzaei et al [ 51 ] also noted that male nurses experienced turnover intention at a higher rate. While two American studies found that seniority in nurses was associated with greater turnover intention [ 34 , 50 ], this was in contrast to findings in a study from Peru [ 67 ], which reported that younger HCWs were more prone to experiencing turnover intention. Social affiliation was also identified by some studies to impact turnover intention, as nurses with strong ties to friends and family perceived greater social support.…”
Section: Resultscontrasting
confidence: 79%
“…Increases in workload were widely found to be positively correlated with turnover intention among HCWs [ 38 , 45 , 55 , 56 ]. In addition, HCWs who worked long hours, or faced an increase in working hours due to the pandemic, were more prone to experiencing turnover intention [ 40 , 50 , 55 , 59 ]. Mirzaei et al [ 51 ] found that job stressors were positively correlated with turnover intention.…”
Section: Resultsmentioning
confidence: 99%
“…When controlling negative affect at work, organisational constraints and interpersonal conflicts at work are not directly related to intention to leave the job or profession. Previous studies have demonstrated direct relationships between job burnout [ 63 ], general job stress [ 64 ], specific interpersonal and organisational stressors, and intention to leave the workplace [ 10 ]. Our findings add to the existing body of knowledge insofar as they suggest that the relationship between stressors and intention to leave the workplace or profession is more complex.…”
Section: Discussionmentioning
confidence: 99%
“…Members of minoritized groups and individuals from communities excluded from economic opportunities may also be at increased risk for adverse mental health impacts from the pandemic. 14,[19][20][21][22][23][24] However, gaps remain in understanding how multiple pandemic-associated hardships, health behavior changes, and coping strategies may co-occur by levels of socioeconomic advantage and/or racial and ethnic group and how these factors are associated with traumatic stress symptoms. The Environmental influences on Child Health Outcomes (ECHO) Program 25,26 follows a diverse multicohort sample and provides an opportunity to understand associations between the COVID-19 pandemic and mothers' psychological health.…”
Section: Introductionmentioning
confidence: 99%